Edukasi Pemanfaatan Tekhnologi Digital dalam Menyusun Menu Gizi Seimbang Bagi Bayi - A. Fahira Nur (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Abstract and Keywords must be written in English, in italic style, and contain a brief description of the research background, objectives, methods, findings, and implications. The abstract is written in one paragraph with a single space (maximum 200 words), without any reference or formula. The Newborn Period (BBL) is a stage that can be called the golden period as well as a critical phase because during this period there is adaptation to the BBL as well as very rapid growth and development. Therefore, it is important to provide a balanced nutritional menu according to BBL's needs to support adequate baby growth and development. In achieving this, breast milk is the main recommendation given immediately after the baby is born until 6 months. Entering the age of 6 months, the baby's nutritional intake needs will increase, so apart from breast milk, MP-ASI becomes an additional menu for babies to support optimal growth and development. However, MP-ASI must be given according to the baby's age and needs. The application for preparing a balanced nutritional menu for babies is a digital technology that is useful for making it easier for mothers to prepare an appropriate and balanced menu for their little ones. By utilizing the digital application